Let $M: P_{1}\rightarrow P_{1}$ be defined by $M(f)=f^{'}+f$, i.e. $M(a_{0}+a_{1}x)=a_{1}+a_{0}+a_{1}x$. Find the adjoint $M^{*}$ of $M$, i.e find $M^{*}(a_{0}+a_{1}x_{1})$, assuming that $L^{2}(0,1)$ inner product is imposed on $P_{1}$. $\langle f(x),g(x)\rangle =\int^{1}_{0}f(x)g(x)dx$.

  • $\begingroup$ This looks like a homework question; please see how to ask such questions. In any case, people here don't tend to like textbook-style problems with no work shown and phrased as commands. $\endgroup$ – Nate Eldredge Jun 10 '13 at 0:37

Let's find an orthogonal basis for the given inner product.
Luckily, $\|1\|=\sqrt{\langle 1,1\rangle}=\sqrt{\int_0^11}=1$. But $x$ is not orthogonal to $1$, so we have to modify it: $$\langle x,1\rangle =\int_0^11\cdot x\,dx=\frac12\,,$$ so that $(x-\frac12)\perp 1$. So is its double, $p:=\,2x-1$. Its norm can be obtained: $\|p\|^2=\|(2x-1)\|^2=\int_0^1(2x-1)^2\,dx=\frac43-2+1=\frac13$.

Then, use the general fact that a vector $v$ can be decomposed in the orthogonal basis $e_1,e_2,...$ as $$v=\frac{\langle v,e_1\rangle}{\|e_1\|^2} e_1+\frac{\langle v,e_2\rangle}{\|e_2\|^2} e_2+\dots$$

So that, now we can apply this to arrive at $M^*$: $$M^*(1)= \langle M^*(1),\,1\rangle\, +3\,\langle M^*(1),\,2x-1\rangle\cdot (2x-1)= \\ = \langle 1,M(1)\rangle+3\,\langle1,M(2x-1)\rangle\cdot(2x-1)\,.$$ Similarly one can obtain $M^*(x)$.

  • $\begingroup$ can you make use of $<M(f),g>=<f,M^{*}(g)>$? $\endgroup$ – 81235 Jun 9 '13 at 23:43
  • $\begingroup$ Didn't I use it? $\endgroup$ – Berci Jun 9 '13 at 23:49
  • $\begingroup$ One can also introduce an orthonormal basis, and work with matrices. Now we can fix $(1,\sqrt3\cdot(2x-1))$, now both these has norm $1$, and are orthogonal to each other (w.r.t. the $L^2$ inner product). Then, coordinating $M$ in this basis, we get $$[M]=\pmatrix{1&2\sqrt3\\0&1}\,$$ so its adjoint (in the same basis!) is $$[M^*]=\pmatrix{1&0\\2\sqrt3&1}\,.$$ Looks odd, but it gives the same as my solution. $\endgroup$ – Berci Jun 10 '13 at 0:00
  • $\begingroup$ My approach: $<M(f),g>=<f,M^{*}(g)>$, $f=a_{0}+a_{1}x$,$g=b_{0}+b_{1}x$, $<M(f),g>=\int^{1}_{0}(a_{1}+a_{0}+a_{1}x)(b_0+b_{1}x)dx$, but I don't how to continue. Can you prove it following my idea? $\endgroup$ – 81235 Jun 10 '13 at 0:02
  • 1
    $\begingroup$ I have read your answer carefully, according your answer,$M^{*}(x)=7x-3$,am I right? $\endgroup$ – 81235 Jun 10 '13 at 0:15

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.